2000
DOI: 10.1002/(sici)1097-4628(20000328)75:13<1577::aid-app3>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on dimensional stability of rat tail tendon collagen fiber

Abstract: ABSTRACT:The organized molecular structure of collagen is related to its dimensional stability. The dimensional stability of collagen arises from the interplay of various intermolecular forces such as covalent, hydrogen bonding, electrostatic interactions, hydrophobic interactions, London or van der Waals forces, and weak interactions. A structure-function relationship exists in collagen. Electrostatic interactions play an important role in dimensional stabilization. The dimensional stability of rat tail tendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Different authors discussed the effect of pH on swelling properties. Usha et al studied the swelling ratio of RTT collagen in acid condition, [18] while Nam et al studied the swelling ratio of collagen gels in function of pH. [42] Even though the pH range was different from the one considered in this work, both these works showed that the swelling ratio was strongly dependent of pH.…”
Section: Mass Changementioning
confidence: 75%
See 1 more Smart Citation
“…Different authors discussed the effect of pH on swelling properties. Usha et al studied the swelling ratio of RTT collagen in acid condition, [18] while Nam et al studied the swelling ratio of collagen gels in function of pH. [42] Even though the pH range was different from the one considered in this work, both these works showed that the swelling ratio was strongly dependent of pH.…”
Section: Mass Changementioning
confidence: 75%
“…[12] Wood et al proved that collagen fibrillogenesis can be favored by pH higher than the isoelectric point, [16] while Roeder et al, [17] Usha et al and Rosenblatt et al discussed the improvement of mechanical properties for collagen matrices when pH was higher than 7. [15,18] Collagen matrices and collagen gel in particular are known to present a time-dependent mechanical behavior. [19][20][21] These viscoelastic properties can be shown by tensile, compression or rheological tests.…”
mentioning
confidence: 99%
“…The dimensional stability of collagenous tissues has been examined under various environmental conditions [7][8][9][10]. The thermally induced structural transitions in the fibrous collagenous network lead to shrinkage process [11].…”
Section: Introductionmentioning
confidence: 99%
“…Obuz et al (2004) reported that response of muscle to heating temperature depends on collagen contents. The authors demonstrated that high collagen content muscle such as biceps femoris was tenderized at 45-65 o C and toughened at [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] o C. On the other hand, longissimus muscle was tenderized at 45-55 o C and toughened at above 55 o C. The studies imply that longer cooking at lower temperature softens collagen components. However if cooking time is extended further, greater myofibril toughening and cooking loss could override the beneficial effect of heat solubilization, resulting in tougher meat.…”
Section: Introductionmentioning
confidence: 99%